Enhancement of fundamental photosynthetic properties, growth and yield in MR219 and MR263 rice varieties via early-stage CO₂ enrichment before transplanting - Muhamad Mujab, Azzami Adam (2022)
Controlled environment systems such as glasshouses regularly utilise elevated CO2 (eCO2) to boost yield and quality in the production of high-value crops. Although this approach is quite commonly practised in commercial horticulture, its implementation on major crops such as rice is technically not feasible, especially elevating CO2 throughout the production field for the entire life cycle of the crop. During the early stage of rice plant development, the structure of the leaf is sensitive to environmental factors, including responses to CO2 levels. In this project, the response of rice seedlings exposed to eCO2 only during the initial nursery phase before field transplant can have a lasting impact until the harvest period was investigated. The study aims include understanding the effects of early-stage eCO2 treatment on rice growth, leaf stomatal properties, photosynthetic performance and yield components at the rice seedling stage and mature stage. This experiment used two local rice varieties, namely MR219 and MR263. Rice plants were grown in a two-stage procedure. First, seedlings were grown in DIY ambient CO2 (400 ppm) and elevated CO2 (~800 ppm) chambers for 24 days and then transplanted to a rain shelter structure where the plants were grown to harvest. The eCO2 source came from the fermentation of a mixture of sugar, distilled water, and baker’s yeast (Saccharomyces cerevisiae) granules. The first experiment showed that eCO2 priming had significantly increased the seedling height (38-42%), the number of leaves (26-30%), leaf thickness (22-38%), leaf length (8-32%) and dry weight (58-69%) for MR219 and MR263 varieties. In general, eCO2 treatment resulted in a larger stomatal complex (14-46%) and stomatal pore area dimensions (62-64%) with reduced stomatal density (11-19%) than aCO2-grown leaves also in both varieties. Moreover, the intrinsic water use efficiency (iWUE) of eCO2 leaves was also 38- 68% higher in both MR219 and MR263. In terms of photosynthetic performance, the maximum assimilation rate (Amax), maximum Rubisco carboxylation rate (Vcmax), maximum electron transport rate (Jmax), the quantum yield of PSII (ΦPSII), and quantum yield of CO2 assimilation (ΦCO2) were significantly higher for eCO2 rice seedlings than aCO2 for both rice varieties. In the second experiment, significant photosynthetic parametres enhancement (Amax, Jmax, ΦPSII, ETR, ΦCO2) were quantified in eCO2 MR263 flag leaves but not in MR219. Interestingly, both rice varieties' seedlings when exposed to eCO2 maintained a significantly higher Vcmax (> 10%) during the mature phase of plant development than plants grown continuously under aCO2. In terms of yield components, both varieties exposed to early-stage eCO2 treatment showed a significantly 14-27% higher filled spikelet number per panicle, 3% higher 1000- grain weight, 11.5-12.5% increase in tillers and 10-12% panicles numbers per plant with significantly 5-6% lower plant height. The yield potential shows an increase of 4-7% for MR219 and MR263 eCO2-treated seedlings compared to aCO2. In conclusion, brief and targeted eCO2 enhancement during the seedlings phase demonstrates a promising way of improving plant growth development, photosynthetic properties and rice yield performance. CO2 priming has been suggested as a potential strategy for improving the productivity of rice crops, especially in regions where maintaining elevated CO2 levels throughout the entire crop life cycle is not feasible or practical. By exposing rice plants to elevated CO2 levels during their early growth stages, farmers may be able to take advantage of the benefits of CO2 priming without having to maintain elevated CO2 levels throughout the entire crop life cycle and, in turn, increase farmers' income. This study can contribute to the development of more sustainable and efficient agricultural practices that can meet the growing demand for food.